Independent Journalism in the History of Indonesian Media Landscape: A Study Case of Kompas Gramedia - Orfinez Nainggolan, Golda Meir; Akim, Akim; Putri Noviasih, Godfrida Winda (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2024)
A complicated combination of political factors, censorship, and the fight for independence has shaped Indonesian journalism history. In this unstable environment, Kompas Gramedia has become a well-known symbol of independent reporting. The history of Kompas Gramedia, one of Indonesia's biggest media conglomerates, from its founding to the present highlights the vital role that the media play in promoting democratic values and guaranteeing the free flow of information. This piece of research explores the development of Kompas Gramedia, emphasizing both the organization's influence on the larger Indonesian media scene and its unwavering dedication to journalistic ethics. The tale of Kompas Gramedia is not only one of a media company's expansion but also a larger one of media freedom in Indonesia. Kompas Gramedia has been instrumental in promoting press freedom and establishing benchmarks for independent journalism, both during the period of severe governmental control and censorship and in the current more liberal and open atmosphere. Through an analysis of the historical background and key turning points in Kompas Gramedia's history, this article offers insights into how independent journalism can flourish in difficult settings and advance a country's socio-political landscape.